Unprecedented growth in the V4 - Is it sustainable? - Stelzigová, Tereza; Bolotov, Ilya; Villaverde Castro, José; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2018)
The dissertation focuses on characteristics of economic growth between 1995 - 2016 and its sustainability which is analysed from the economic perspective only. Firstly, the paper provides a literature review where foreign direct investment was identified as the main driver of economic growth in the V4. The methodologies that have been used to achieve the determinants and policy recommendations for sustainability of growth were collected. Secondly, respective analysis comparing two models based on the Total Economy Database and the Penn World Tables data is introduced. Thirdly, the results and selected aspects were linked together in the graphical analysis. The main results are that FDI was found to be the most important driver in the V4, however its role is diminishing. The initial growth was driven by total factor productivity which contribution has rapidly declined during the analysed period but has not been offset by other inputs causing GDP growth rate to decline. The sustainability conclusion is such that the FDI has probably successfully transferred the knowledge into domestic environment and if TFP will not be spurred by domestic activity, GDP growth rate will probably stabilize at lower yet sustainable level referring to higher development of the region.
Vedoucí práce: Ilya Bolotov
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: economics of globalisation and european integration [obor dipl. práce]; diplomové práce; master's theses